2015
DOI: 10.1016/j.pjnns.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the conversion of mild cognitive impairment to Alzheimer's disease based on the volumetric measurements of the selected brain structures in magnetic resonance imaging

Abstract: Volumetric measurements may help clinicians to predict MCI conversion to AD but due to low sensitivity it cannot be use separately. The study group requires further observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…However, the biggest limitation of our study was the small group of patients (40 persons), so the results are limited. Surprisingly, sensitivity for volumetric measurements was almost 90%, whereas in our previous study (101 patients diagnosed with MCI) we have obtained sensitivity of 64.7%, specificity of 96.4% and classification rate of 91% (in this study 90%) [11]. Similar results using volumetry were presented by Convit.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, the biggest limitation of our study was the small group of patients (40 persons), so the results are limited. Surprisingly, sensitivity for volumetric measurements was almost 90%, whereas in our previous study (101 patients diagnosed with MCI) we have obtained sensitivity of 64.7%, specificity of 96.4% and classification rate of 91% (in this study 90%) [11]. Similar results using volumetry were presented by Convit.…”
Section: Discussionsupporting
confidence: 78%
“…Taking into account individual volumetric measurements the results obtained in our previous study were confirmed, i.e. the highest sensitivity was for the hippocampus and then for the left entorhinal cortex [11]. Our results are contrary to the results presented by Dickerson (23 patients diagnosed with MCI, observation period of 12-77 months) or Stoub (23 patients diagnosed with MCI and 35 from the control group, observation period was 5 years) in whose studies volume of …”
Section: Discussionsupporting
confidence: 59%
“…Different investigations demonstrate that this decrease is present many years before symptoms' onset and presents a high positive predictive value for the progression from MCI to AD [27,28]. A number of evidence arising from amyloid positron emission tomography abnormalities, CSF fluorodeoxyglucose-positron emission tomography hypometabolism, volume and atrophy rate markers derived from structural MRI in MCI patients suggest the possibility to use functional and anatomic cerebral changes to predict a conversion to AD [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, atrophy advances to the remainder of the MTL where grey matter (GM) loss occurs in the medial temporal gyrus, parahippocampus, parahippocampal and fusiform gyri, and temporal pole [9]. Nesteruk and colleagues [10] found that MTL atrophy discriminates those who will convert from MCI to AD from non-converters. It also differentiates AD from dementia with Lewy bodies (DLB) and Parkinson’s disease with dementia (PDD), where AD patients show the greatest reductions in hippocampal volume [11, 12].…”
Section: Structural Imagingmentioning
confidence: 99%